The Implementation of Supply Chain Collaboration for Green Supply Chain: The Qualitative Case Study Research for Fast-Moving Consumer Goods Sector - Xia, Guijin (2022)
The fast-moving consumer goods (FMCG) industry is criticized for severe environmental pollution problems, so achieving environmentally sustainable operations is a focal point within the industry. This dissertation aims to identify how companies in the fast-moving consumer goods (FMCG) sector achieve a green supply chain through supply chain collaboration.